Financial management and profitability of a food supplier company - García Grández, Horacio (2022)
Objective: to determine the incidence of financial management on the profitability of a food supplier company, 2021. Methodology: it consisted of an applied study, quantitative approach, descriptive-explanatory level, non-experimental design, and cross-section. The population consisted of 15 workers, the sample included only 3, being the manager, accountant and administrator. The data collection techniques were the interview, observation and documentary analysis. Results: they revealed that financial management is deficient by 44%, reflecting inadequate management of current resources. On the other hand, the performance was not expected in the last 2 years. Conclusion: financial management has a positive impact on the profitability of the food supplier company, which was determined from the adjustment of the losses in each of the current resources in the financial statements, being analyzed with the application of performance indicators. . In this sense, reference is made to the fact that if the company had taken the necessary measures and had efficient control of all its current resources, the utility could have been higher than what was analyzed in the last fiscal year.